Adapting Statistical Science for a Fast-Changing Climate. Issue 1 (2nd January 2023) - Cressie, Noel
Abstract: We have been looking up at the stars for millennia, trying to figure out our place in space, making small steps out and sending probes out even further. We are space travelers and, for the foreseeable future, Earth is our "mother ship." To sustain our voyage through space, we need to look out for stressors, overheating and, particularly, new energy sources for our ship. We need to monitor its integrity, repair components that are broken, and establish long-term maintenance protocols. That is, mitigation is needed at scale, and we need to plan and action it now! We have scientific knowledge about different parts of the ship with differing degrees of certainty, but the message is clear that it is in peril from overheating. Unfortunately, there are many captains to report to, with different priorities. While they demur, deflect, and disagree, Earth is rapidly approaching a waypoint where mitigation will not be enough, and adaptation for a fast-changing climate will be part of our future.